Too civil to care? How online hate speech against different social groups affects bystander intervention - Obermaier, Magdalena (European journal of criminology, 2023)
A large share of online users has already witnessed online hate speech. Because targets tend to interpret such bystanders? lack of reaction as agreement with the hate speech, bystander intervention in online hate speech is crucial as it can help alleviate negative consequences. Despite evidence regarding online bystander intervention, however, whether bystanders evaluate online hate speech targeting different social groups as equally uncivil and, thereby, equally worthy of intervention remains largely unclear. Thus, we conducted an online experiment systematically varying the type of online hate speech as homophobia, racism, and misogyny. The results demonstrate that, although all three forms were perceived as uncivil, homophobic hate speech was perceived to be less uncivil than hate speech against women. Consequently, misogynist hate speech, compared to homophobic hate speech, increased feelings of personal responsibility and, in turn, boosted willingness to confront.